"Brooke has been an Absolute Angel" - Leniency and the Halo Effect in Industry BasedAssessment of Student Competencies - Wolf, Katharina (WACE, 2012)
Industry placements are popular means to provide students with an opportunity to apply their skills, knowledge and experience in a “real world” setting. Within this context, supervisor feedback allows educators to measure students’ performance beyond academic objectives, by benchmarking it against industry expectations. However, industry assessments appear to be frequently clouded and overwhelmingly positive by nature, which questions the reliability and validity of supervisors’ judgment of competencies. Leniency bias is the reluctance to assign low or fail grades to students, whilst the halo bias refers to an overall positive impression of a student who may have done well in one competency area, which consequently clouds the assessment of other competencies. Supervisor bias has been paid much attention within the context of clinical placements, as well as within the domain of social work. However, they have been largely ignored within business education, despite the increasing emphasis on and deep integration of work integrated learning in the business curriculum. This paper sets out to address this gap by examining the impact of the leniency and halo effect in the context of a final year, compulsory placement unit, based on observations and data collected over four semesters, across five campuses (N=371). The focus of this project is less on the reliability of existing measures, than on gaining an understanding of the reasons behind assessment bias and the pressures placed on industry assessors. The author concludes that although industry supervisors play a crucial role in higher education, their needs have to date been largely ignored.